Weakening of the Kuroshio Upstream by Cyclonic Cold Eddies Enhanced by the Consecutive Passages of Typhoons Danas, Wipha, and Francisco (2013) - Jeon, Chanhyung; Watts, D. Randolph; Min, Hong Sik; Kim, Dong Guk; Kang, Sok Kuh; Moon, Il-Ju; Park, Jae-Hun (Frontiers in Marine Science, 2022)
An array of five pressure-recording inverted echo sounder (PIES) moorings spanning a distance of 420 km around the subtropical countercurrent and North Equatorial Current regions of the western Pacific detected extraordinary sea level drops from November to December 2013. In October 2013, three typhoons, namely, Danas, Wipha, and Francisco, consecutively passed east of the PIES sites, which significantly strengthened pre-existing cyclonic cold eddies to create the observed sea level drops. The typhoon-strengthened cold eddies propagated westward over approximately 1000 km for approximately 4 months and eventually met the Kuroshio offshore Taiwan. The approaching eddies interacted with the Kuroshio upstream for 3 months and reduced the Kuroshio intensity by up to 24% in February–May 2014, the lowest record for the last 26 years of satellite measurements. Our results can provide a new mechanism linking typhoon-to-eddy-to-Kuroshio variability through oceanic processes.